Book Review of "A Practical Introduction to Homeland Security: Home and Abroad" by Bruce Oliver Newsome and Jack A. Jarmon - Shrujana Senthil (International Journal of Nuclear Security, 2021)
In A Practical Introduction to Homeland Security: Home and Abroad, authors Bruce Oliver Newsome and Jack A. Jarmon provide a well thought-out, in-depth analysis of key components that need to be understood when it comes to the state and workings of homeland security as well as its international connections. They break down different concepts that make up this broad unit in a structured way that allows for readers interested in the subject to focus on a specific category, making the reading material easier to approach. Both Newsome and Jarmon have written other works regarding international relations and national security. This work, however, contains a more holistic, general idea of the topics for anyone who wishes to become familiar with the basic concepts within these sectors.